Insights on the heterogeneity of thermal transfer in the chalk aquifer using fibre-optic distributed temperature sensing - Katerina Kyrkou; Joseph Kelly; Adam Booth; Fleur Loveridge; David Boon; Edward Hough; Lawrence Scott; Matthew Jackson; Adrian Butler; Daniel Perez; Athena Chalari (Geothermics, 2026)

Global sensitivity analysis workflows and rankings: A practical comparison for researchers - Ken B. Newman; Shaini Naha; Leah A. Jackson-Blake; Cairistiona Topp; Miriam Glendell; Adam Butler (Environmental Modelling & Software, 2026)

Population genetic structure of male eastern Wild Turkeys in Mississippi - Annie Farrell; Xueyan Shan; Adam Butler; Scott Rush; Dave Godwin; Guiming Wang (Journal of Ornithology, 2026)

Effects of environmental conditions on mate fidelity in a socially monogamous seabird - Sue Lewis; Adam Butler; Sarah Wanless; Mark A. Newell; Michael P. Harris; Sarah J. Burthe; Carrie M. Gunn; Richard J. Howells; Francis Daunt (Animal Behaviour, 2025)

Survival Estimates of Endangered Shortnose Sturgeon (Acipenser brevirostrum Lesueur, 1818) from Geographically Disjunct Population Segments - Evan C. Ingram; Amanda L. Higgs; Liam Butler; Dewayne A. Fox; Adam G. Fox (Fishes, 2025)
The complex life history and stock structure of endangered shortnose sturgeon (Acipenser brevirostrum) may hinder recovery efforts for individually managed river populations in the US. Reliable survival estimates are essential for evaluating population trends and guiding conservation amid ongoing and emergent threats. However, such estimates are scarce in the recent literature and available for only a few wild populations, with their usefulness in practical management limited. In this study, we leverage multi-year acoustic telemetry data from monitoring projects in the Hudson River, New York (2012–2015), and Altamaha River, Georgia (2011–2014), to develop and compare survival estimates for spawning populations at opposite ends of the species’ US geographic range. Bayesian multistate capture–recapture models indicated high and precise apparent monthly adult survival in both the Hudson (0.991; 95% Bayesian credibility interval [CI]: 0.984–0.996) and Altamaha (0.980; 95% CI: 0.969–0.989) rivers, with implied annual survival rates of 0.897 and 0.787, respectively. Overall, this study advances our understanding of clinal variation in key demographic parameters and underscores the need to develop regionally specific goals for recovery. Broadening the estimates through increased telemetry coverage and integration of additional data will strengthen recovery efforts and support the long-term persistence of shortnose sturgeon across their range.

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Quantifying myelin density in the feline auditory cortex - Austin Robertson; Daniel J. Miller; Adam Hull; Blake E. Butler (Brain Structure and Function, 2024)

Effects of a fishery closure and prey abundance on seabird diet and breeding success: Implications for strategic fisheries management and seabird conservation - Kate R. Searle; Charlotte E. Regan; Martin R. Perrow; Adam Butler; Anna Rindorf; Michael P. Harris; Mark A. Newell; Sarah Wanless; Francis Daunt (Biological Conservation, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Comparison of blood cultures versus T2 Candida Panel in management of candidemia at a large community hospital - Taylor D. Steuber; Lauren Butler; Adam Sawyer; Rachel Chappell; Jonathan Edwards (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Sublethal effects of natural parasitism act through maternal, but not paternal, reproductive success in a wild population - Olivia Hicks; Jonathan A. Green; Francis Daunt; Emma J. A. Cunningham; Mark Newell; Adam Butler; Sarah J. Burthe (Ecology, 2019)
Parasites are a major component of all animal populations. Males and females often differ in their levels of parasite prevalence, potentially leading to sex differences in the impact of parasitism on fitness, with important implications for the evolution of parasite and host traits including resistance, tolerance, and virulence. However, quantitative measures of the impact of parasitism under free‐living conditions are extremely rare, as they require detailed host demographic data with measures of parasite burden over time. Here, we use endoscopy for direct quantification of natural‐parasite burdens and relate these to reproductive success over 7 yr in a wild population of seabirds. Contrary to predictions, only female burdens were associated with negative impacts of parasitism on breeding success, despite males having significantly higher burdens. Female reproductive success declined by 30% across the range of natural parasite burdens. These effects persisted when accounting for interannual population differences in breeding success. Our results provide quantitative estimates of profound sub‐lethal effects of parasitism on the population. Importantly, they highlight how parasites act unpredictably to shape ecological and evolutionary processes in different components of the same population, with implications for demography and selection on host and parasite traits.

Correction to: Pronounced long-term trends in year-round diet composition of the European shag Phalacrocorax aristotelis - Richard J. Howells; Sarah J. Burthe; Jonathan A. Green; Michael P. Harris; Mark A. Newell; Adam Butler; Sarah Wanless; Francis Daunt (Marine Biology, 2019)

Pronounced long-term trends in year-round diet composition of the European shag Phalacrocorax aristotelis - Richard J. Howells; Sarah J. Burthe; Jonathan A. Green; Michael P. Harris; Mark A. Newell; Adam Butler; Sarah Wanless; Francis Daunt (Marine Biology, 2018)

Rice ecosystem services in South-east Asia - Josef Settele; Kong Luen Heong; Ingolf Kühn; Stefan Klotz; Joachim H. Spangenberg; Gertrudo Arida; Alexis Beaurepaire; Silke Beck; Erwin Bergmeier; Benjamin Burkhard; Roland Brandl; Jesus Victor Bustamante; et al. (Paddy and Water Environment, 2018)

Assessing uncertainties in land cover projections - Peter Alexander; Reinhard Prestele; Peter H. Verburg; Almut Arneth; Claudia Baranzelli; Filipe Batista e Silva; Calum Brown; Adam Butler; Katherine Calvin; Nicolas Dendoncker; Jonathan C. Doelman; Robert Dunford; et al. (Global Change Biology, 2017)
Understanding uncertainties in land cover projections is critical to investigating land‐based climate mitigation policies, assessing the potential of climate adaptation strategies and quantifying the impacts of land cover change on the climate system. Here, we identify and quantify uncertainties in global and European land cover projections over a diverse range of model types and scenarios, extending the analysis beyond the agro‐economic models included in previous comparisons. The results from 75 simulations over 18 models are analysed and show a large range in land cover area projections, with the highest variability occurring in future cropland areas. We demonstrate systematic differences in land cover areas associated with the characteristics of the modelling approach, which is at least as great as the differences attributed to the scenario variations. The results lead us to conclude that a higher degree of uncertainty exists in land use projections than currently included in climate or earth system projections. To account for land use uncertainty, it is recommended to use a diverse set of models and approaches when assessing the potential impacts of land cover change on future climate. Additionally, further work is needed to better understand the assumptions driving land use model results and reveal the causes of uncertainty in more depth, to help reduce model uncertainty and improve the projections of land cover.

Biogeographic variability in the physiological response of the cold‐water coral L ophelia pertusa to ocean acidification - Samuel E. Georgian; Sam Dupont; Melissa Kurman; Adam Butler; Susanna M. Strömberg; Ann I. Larsson; Erik E. Cordes (Marine Ecology, 2016)
While ocean acidification is a global issue, the severity of ecosystem effects is likely to vary considerably at regional scales. The lack of understanding of how biogeographically separated populations will respond to acidification hampers our ability to predict the future of vital ecosystems. Cold‐water corals are important drivers of biodiversity in ocean basins across the world and are considered one of the most vulnerable ecosystems to ocean acidification. We tested the short‐term physiological response of the cold‐water coral Lophelia pertusa to three pH treatments (pH = 7.9, 7.75 and 7.6) for Gulf of Mexico (USA) and Tisler Reef (Norway) populations, and found that reductions in seawater pH elicited contrasting responses. Gulf of Mexico corals exhibited reductions in net calcification, respiration and prey capture rates with decreasing pH. In contrast, Tisler Reef corals showed only slight reductions in net calcification rates under decreased pH conditions while significantly elevating respiration and capture rates. These differences are likely the result of environmental differences (depth, pH, food supply) between the two regions, invoking the potential for local adaptation or acclimatization to alter their response to global change. However, it is also possible that variations in the methodology used in the experiments contributed to the observed differences. Regardless, these results provide insights into the resilience of L. pertusa to ocean acidification as well as the potential influence of regional differences on the viability of species in future oceans.

The impact of flood action groups on the uptake of flood management measures - Ruth Dittrich; Anita Wreford; Adam Butler; Dominic Moran (Climatic Change, 2016)

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

Landscape and climate determine patterns of spread for all colour morphs of the alien ladybird Harmonia axyridis - Bethan V. Purse; Richard Comont; Adam Butler; Peter M. J. Brown; Clare Kessel; Helen E. Roy (Journal of Biogeography, 2015)
Aim Understanding why some areas are more vulnerable to invasion by invasive alien species than others represents a key challenge in invasion biology. We investigated the roles of landscape, climate, proximity to initial invasion sites, recording intensity and colour pattern polymorphism in explaining the spread of the invasive ladybird Harmonia axyridis across Great Britain. Location The British mainland and inshore islands (Anglesey, Isle of Wight and the Inner Hebrides). Methods Patterns in time to invasion of H. axyridis were quantified at a hectad level (10 km grid squares) from over 23,000 records. Bayesian spatial survival models were developed relating spread patterns to concurrent patterns in climate, land cover and recording intensity. Separate models were developed for melanic (f. conspicua and f. spectabilis ) and non‐melanic (f. succinea ) colour forms that were hypothesized to differ in their response to climate factors, particularly temperature, and subsequent spread. Results Harmonia axyridis spread more rapidly into hectads containing a high proportion of urban land cover and marginally more slowly into hectads containing high conifer cover. Invasions were recorded more rapidly in hectads with high recording intensity, or that were close to initial invasion sites. Harmonia axyridis colour morphs spread to similar extents, although increased sunshine significantly enhanced the spread of the non‐melanic form (f. succinea ). Correspondence between observed and predicted times of invasion from survival models was substantial (Pearson's r p for all H. axyridis colour forms = 0.834). Main conclusions The ability of H. axyridis to use a wide range of habitats and prey species and overwinter inside buildings may have allowed this species to establish rapidly in urban areas. Native ladybird species in urban areas may suffer combined negative impacts of habitat deterioration and competition from H. axyridis . Spatial survival models help us to identify areas vulnerable to invasion and to understand the impacts of multiple environmental drivers on the spread of invasive alien species, given detailed data on time to invasion.